2015
DOI: 10.1186/s12905-015-0236-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of domestic violence and alcohol consumption among women and the effectiveness of a brief intervention in a household setting: a protocol study

Abstract: BackgroundDomestic violence and harmful alcohol consumption are considered major public health problems worldwide. These phenomena often co-occur, and they share several risk factors. Nevertheless, few in-depth studies have supported integrated interventions for both phenomena, in particular among Latin American women. This project will study the consumption of alcoholic beverages among women and its relationship with patterns of domestic violence; furthermore, it will assess the effect of a brief intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
0
8
0
3
Order By: Relevance
“…We used a combination of quantitative and qualitative methods in our study, in a follow-up of a previous research's sample (Gebara et al, 2015). Initially, a survey was conductedin 2011/2012 -with a representative household sample from two neighborhoods with different socioeconomic profiles in a medium-sized city in the state of Minas Gerais (Gebara et al, 2015). This investigation addressed patterns of domestic violence and alcohol use among women and involved 905 participants.…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a combination of quantitative and qualitative methods in our study, in a follow-up of a previous research's sample (Gebara et al, 2015). Initially, a survey was conductedin 2011/2012 -with a representative household sample from two neighborhoods with different socioeconomic profiles in a medium-sized city in the state of Minas Gerais (Gebara et al, 2015). This investigation addressed patterns of domestic violence and alcohol use among women and involved 905 participants.…”
Section: Methods Participantsmentioning
confidence: 99%
“…In this regard, it is important to examine the possibility that expectancies related to outcomes of alcohol use play a role in intimate partner violence, in addition to the effects of the use itself (Brasfield et al, 2016). Research suggests that the relationship between the use of alcoholic beverages and violent behavior is complex and non-linear (Brasfield et al, 2016;Capaldi et al, 2011;Gebara et al, 2015), being influenced, among other factors, by the amount of alcohol ingested.…”
Section: Contexts/triggers Of Intimate Partner Physical Violencementioning
confidence: 99%
“…The sample calculation considered 3% maximum error desired for the study, 95% confi dence level, correction for fi nite populations, sample plan eff ect equal to 2, and losses due to refusal of approximately 25%. Further information about the research protocol can be found in a previous publication (Gebara et al, 2015).…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…Considering that cross-ethnic studies have estimated the prevalence of depression ranging from 1.5 to 32% across ethnicities (25), accurate measurement of depression as well as depressive symptoms across racial and ethnic groups has attracted special attention (613). The Center for Epidemiologic Studies Depression scale (CES-D) is one of the most commonly used tools for measuring depressive symptoms in epidemiological (13) as well as clinical (14) studies. Since the introduction of the original 20-item CES-D scale, which evaluates major domains of depressive symptoms (i.e., 7 items of negative affect, 4 items of positive affect, 7 items of somatic symptoms, and 2 items of interpersonal problems), different abbreviated versions with variable number of items have been applied in epidemiological studies, (1325) among them the widely used 20-item and 10-item CES-D scales (13, 19).…”
Section: Introductionmentioning
confidence: 99%